The politicians' perspectives on participation in mammographic screening: an interview-based study from a region in Sweden - Maria Norfjord van Zyl; Per Tillgren; Margareta Asp (BMC, 2021)
Abstract Background Breast cancer is the most common cancer type among women globally. To facilitate early detection, all 40-74-year-old female residents of Sweden are invited to participate in a population-based mammographic screening programme. Approximately 20% of all invited women decline the offer, and if this is due to systematic differences that can be adjusted, it can indicate inequity in healthcare. Assessment of and being updated about the health and healthcare of the residents are largely the responsibilities of the self-governed regions in Sweden. The understanding of the residents' health serves as a basis for decision making and priority setting. This study aims to describe how politicians representing a region in Sweden perceive women's participation in mammographic screening and the politicians' own possibility to promote such participation. Methods Qualitative thematic analysis was conducted on the data obtained from individual semi-structured interviews held in 2019. The interviewees comprised ten politicians (six women and four men, 38-71 years old) representing a sub-committee focusing on public health and healthcare issues. Results Two main themes have been identified: 1) expected actions and 2) expected conditions for acting, including a total of four sub-themes. According to the politicians, the expected actions, such as obtaining information and being updated about matters regarding mammographic screening, concern both the women invited to the screening and the politicians themselves. Additionally, for both the individual and the healthcare organisation, here represented by the politicians, expected actions entail a shared commitment to maintain health. The expected conditions for acting refer to the politician's awareness of the factors influencing the women's decision to undergo or refuse the screening and having the resources to enable taking actions to facilitate participation. Conclusions Expected actions and expected conditions for acting are tightly connected and entail some form of prioritisation by the politicians. Setting the priorities can be based on information about the purpose of the screening and an understanding of social determinants' impacts on women's decision to refrain from mammographic screening, as well as available resources.